Determinants of future anxiety across individual, household, and regional levels in South Korea using a social ecological model - Hyun Woo Jung; Minsu Choi; Kwang-Soo Lee (Scientific Reports)
Abstract This study is the first to examine the determinants of future anxiety in South Korea using the Social Ecological Model (SEM). It aimed to show that, beyond individual factors, mezzo- and macro-level aspects, particularly those related to housing, may influence anxiety. Utilizing 2018 data from the Korean Health Panel Survey, we employed a three-level multilevel analysis to investigate how these factors contribute to the perception of future anxiety among Koreans. Our findings reveal that future anxiety is influenced by a complex interplay of demographic and socio-economic factors, including gender, age, health status, economic stability, living conditions, and regional socio-economic indicators. Notably, the study highlights the significant role of household-level factors, such as income and housing status, in shaping individuals’ anxieties about the future. Additionally, regional characteristics like housing vacancy rates and suicide rates are found to have an impact, suggesting the importance of broader socio-economic and cultural contexts in understanding future anxiety. Given South Korea’s socio-economic challenges, including the real estate crisis and demographic shifts, our study underscores the need for targeted policies to alleviate future anxiety, enhance mental well-being, and promote a more equitable society.